Protothecal peritonitis in child after bone marrow transplantation: case report and literature review of paediatric cases. Issue 6 (14th September 2014) - Sykora, T.; Horakova, J.; Buzzasyova, D.; Sladekova, M.; Poczova, M.; Sufliarska, S.
Abstract The case presented here illustrates a protothecal infection caused by Prototheca wickerhamii in a paediatric haematopoietic stem cell recipient followed by a review of the literature of all 13 paediatric cases published since 1980. Protothecosis is a rare disease caused by algae, not described in this setting before. Infection was proven additionally post‐mortem from peritoneal dialysis fluid. Even though no death of a paediatric patient due to this infection has been reported and the mortality rate associated with protothecosis is low, our patient died from multiorgan failure as a result of numerous post‐transplant complications and a strain of cultivated alga that was highly resistant to antifungal agents. Prototheca spp. show various susceptibility profiles, and there is no direct correlation between in vitro activity and clinical response. There are different treatment regimens described but there are no clear published guidelines of specific therapy of protothecosis. Paediatric cases were successfully treated mostly with amphotericin B and azoles. As the number of immunocompromised patients increases, it is necessary to think more about unusual pathogens such as Prototheca.